Transcript and protein marker patterns for the identification of steatotic compounds in human HepaRG cells. (November 2020) - Lichtenstein, Dajana; Mentz, Almut; Schmidt, Felix F.; Luckert, Claudia; Buhrke, Thorsten; Marx-Stoelting, Philip; Kalinowski, Joern; Albaum, Stefan P.; Joos, Thomas O.; Poetz, Oliver; Braeuning, Albert
Abstract: Non-alcoholic fatty liver disease is a major health concern especially in Western countries. Animal studies suggest that certain chemicals may contribute to hepatocellular triglyceride accumulation, among them a number of hepatotoxic pesticidal active compounds. In order to improve the identification of potential liver steatosis inducers in vitro in a human cell culture system, HepaRG cells were treated with a selection of 30 steatotic or non-steatotic pesticides. Induction of triglyceride accumulation was monitored, and changes in the expression of hepatotoxicity marker genes were measured at the mRNA and protein levels. Based on these data, transcript and protein marker signatures predictive of triglyceride accumulation in HepaRG cells were derived. The predictive transcript set consisted of POR, ANXA10, ARG1, CCL20, FASN, INSIG1, SREBF1, CD36, CYP2D6, and SLCO1B1 . The predictive protein set consisted of NCPR ( POR ), CYP2E1, CYP1A1, ALDH3A1, UGT2B7, UGT2B15, S100P, LMNA, and PRKDC. In conclusion, the present study presents for the first time transcript and protein marker patterns to separate steatotic from non-steatotic compounds in a human liver cell line. Highlights: 30 pesticides were screened for in vitro triglyceride accumulation. mRNA and protein marker patterns for triglyceride accumulation were identified. In vitro data showed good correlation to in vivo observation.